Global, regional, and national quality of care index of cervical and ovarian cancer: a systematic analysis for the global burden of disease study 1990-2019 - Mohammadreza Azangou-Khyavy; Erfan Ghasemi; Negar Rezaei; Javad Khanali; Ali-Asghar Kolahi; Mohammad-Reza Malekpour; Mahsa Heidari‐Foroozan; Maryam Nasserinejad; Esmaeil Mohammadi; Mohsen Abbasi-Kangevari; Seyyed-Hadi Ghamari; Narges Ebrahimi; et al. (BMC, 2024)
Abstract Background and objective Cervical cancer is the most preventable and ovarian cancer is the most lethal gynecological cancer. However, in the world, there are disparities in health care performances resulting in differences in the burden of these cancers. The objective of this study was to compare the health-system quality of care and inequities for these cancers using the Quality of Care Index (QCI). Material and methods The 1990-2019 data of the Global Burden of Disease (GBD) was analyzed to extract rates of incidence, prevalence, mortality, Disability-Adjusted Life Years (DALYs), Years of Life Lost (YLL), and Years of healthy life lost due to disability (YLD) of cervical and ovarian cancer. Four indices were developed as a proxy for the quality of care using the above-mentioned rates. Thereafter, a Principal Components Analysis (PCA) was applied to construct the Quality of Care Index (QCI) as a summary measure of the developed indices. Results The incidence of cervical cancer decreased from 1990 to 2019, whereas the incidence of ovarian cancer increased between these years. However, the mortality rate of both cancers decreased in this interval. The global age-standardized QCI for cervical cancer and ovarian cancer were 43.1 and 48.5 in 1990 and increased to 58.5 and 58.4 in 2019, respectively. QCI for cervical cancer and ovarian cancer generally decreased with aging, and different age groups had inequitable QCIs. Higher-income countries generally had higher QCIs for both cancers, but exceptions were also observed. Conclusions Uncovering disparities in cervical and ovarian cancer care across locations, Socio-Demographic Index levels, and age groups necessitate urgent improvements in healthcare systems for equitable care. These findings underscore the need for targeted interventions and prompt future research to explore root causes and effective strategies for narrowing these gaps.